Comorbid Conditions in Idiopathic Pulmonary Fibrosis: Recognition and Management - Oldham, Justin M.; Collard, Harold R. (Frontiers in Medicine, 2017)
Idiopathic Pulmonary Fibrosis (IPF), a fibrosing interstitial pneumonia of unknown etiology, primarily affects older adults and leads to a progressive decline in lung function and quality of life. With a median survival of 3-5 years, IPF is the most common and deadly of the idiopathic interstitial pneumonias. Despite the poor survivorship, there exists substantial variation in disease progression, making accurate prognostication difficult. Lung transplantation remains the sole curative intervention in IPF, but two anti-fibrotic therapies were recently shown to slow pulmonary function decline and are now approved for the treatment of IPF in many countries around the world. While the approval of these therapies represents an important first step in combatting of this devastating disease, a comprehensive approach to diagnosing and treating patients with IPF remains critically important. Included in this comprehensive assessment is the recognition and appropriate management of comorbid conditions. Though IPF is characterized by single organ involvement, many comorbid conditions occur within other organ systems. Common cardiovascular processes include coronary artery disease and pulmonary hypertension, while gastroesophageal reflux and hiatal hernia are the most commonly encountered gastrointestinal disorders. Hematologic abnormalities appear to place patients with IPF at increased risk of venous thromboembolism, while diabetes mellitus and hypothyroidism are prevalent metabolic disorders. Several pulmonary comorbidities have also been linked to IPF, and include emphysema, lung cancer and obstructive sleep apnea. While the treatment of some comorbid conditions such as coronary artery disease, diabetes mellitus and hypothyroidism is recommended irrespective of IPF, the benefit of treating others, such as gastroesophageal reflux and pulmonary hypertension, remains unclear. In this review we highlight common comorbid conditions encountered in IPF, discuss disease-specific diagnostic modalities and review the current state of treatment data for several key comorbidities.